New Evidence on Employment Effects of Informal Care Provision in Europe - Kolodziej, Ingo WK; Reichert, Arndt R; Schmitz, Hendrik (Health services research)

Information, Risk Aversion, and Health Care Economics - Schmitz, Hendrik; Winkler, Svenja (Oxford Research Encyclopedia of Economics and Finance)

Human-induced climate change: the impact of land-use change - Gries, Thomas; Redlin, Margarete; Ugarte, Juliette Espinosa (Theoretical and Applied Climatology)

Machine learning and natural language processing on the patent corpus: Data, tools, and new measures - Balsmeier, Benjamin; Assaf, Mohamad; Chesebro, Tyler; Fierro, Gabe; Johnson, Kevin; Johnson, Scott; Li, Guan‐Cheng; Lück, Sonja; O'Reagan, Doug; Yeh, Bill; Zang, Guangzheng; Fleming, Lee (Journal of Economics & Management Strategy)
Drawing upon recent advances in machine learning and natural language processing, we introduce new tools that automatically ingest, parse, disambiguate, and build an updated database using U.S. patent data. The tools identify unique inventor, assignee, and location entities mentioned on each granted U.S. patent from 1976 to 2016. We describe data flow, algorithms, user interfaces, descriptive statistics, and a novelty measure based on the first appearance of a word in the patent corpus. We illustrate an automated coinventor network mapping tool and visualize trends in patenting over the last 40 years.
Keywords: Management of Technology and Innovation; Strategy and Management; Economics and Econometrics; General Business; Management and Accounting; General Medicine

On the relevance of contextual factors for socially responsible investments: an econometric analysis - Gutsche, Gunnar; Köbrich León, Anja; Ziegler, Andreas (Oxford Economic Papers)

Slow Booms and Deep Busts: 160 Years of Business Cycles in Spain - Gries, Thomas; Fritz, Marlon; Feng, Yuanhua (Review of Economics)

A general class of SemiGARCH models based on the Box-Cox transformation - Zhang, Xuehai; Feng, Yuanhua; Peitz, Christian

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas

Sick already? Job loss makes it even worse - Schmitz, Hendrik; Schiele, Valentin (Atlas of Science)

Preis, Service oder Leistungen: Was beeinflusst besonders die Krankenkassenwahl von gesetzlich Versicherten? - Schmitz, Hendrik (Krankenversicherung im Rating)

The effects of competition on medical service provision - Brosig-Koch, Janet; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We explore how competition between physicians affects medical service provision. Previous research has shown that, without competition, physicians deviate from patient‐optimal treatment under payment systems like capitation and fee‐for‐service. Although competition might reduce these distortions, physicians usually interact with each other repeatedly over time and only a fraction of patients switches providers at all. Both patterns might prevent competition to work in the desired direction. To analyze the behavioral effects of competition, we develop a theoretical benchmark that is then tested in a controlled laboratory experiment. Experimental conditions vary physician payment and patient characteristics. Real patients benefit from provision decisions made in the experiment. Our results reveal that, in line with the theoretical prediction, introducing competition can reduce overprovision and underprovision, respectively. The observed effects depend on patient characteristics and the payment system, though. Tacit collusion is observed and particularly pronounced with fee‐for‐service payment, but it appears to be less frequent than in related experimental research on price competition.

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarboe, Oddvar

Evolutionary Equilibrium in Stochastic Contests - Entry, Effort, and Overdissipation - Gu, Yiguan; Hehenkamp, Burkhard; Leininger, Wolfgang

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Innovations, growth and participation in advanced economies - a review of major concepts and findings - Gries, T.; Grundmann, R.; Palnau, Irene; Redlin, Margarete (International Economics and Economic Policy)

Does Price Framing Affect the Consumer Price Sensitivity of Health Plan Choice? - Schmitz, Hendrik; Ziebarth, Nicolas R. (Journal of Human Resources)

Informal Care and Long-term Labor Market Outcomes - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

On the interdependence of ambulatory and hospital care in the German health system - Büyükdurmus, Tugba; Kopetsch, Thomas; Schmitz, Hendrik; Tauchmann, Harald (Health Economics Review)

Technology diffusion, international integration and participation in developing economies - a review of major concepts and findings - Gries, Thomas; Grundmann, R.; Palnau, Irene; Redlin, Margarete (International Economics and Economic Policy)

Towards an Economic Theory of Destabilization War - Gries, Thomas; Haake, Claus-Jochen (Peace Economics, Peace Science and Public Policy)